Effective promotion of renewable energy in the presence of an emissions trading system: [analysis of the success of ETS and promotion of renewable energy as overlapping regulations in Germany - adjustment of the ETS] - Sebastian Schäfer (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
This paper contributes to the literature of overlapping regulations as we introduce a model, which gives insights in an effective combination of the EU emissions trading system (ETS) and the promotion of renew- able energy within the electricity sector. Under consideration of EU long term objectives in CO2 mitigation we evaluate the efficient share of renewable energy. Hence, we give rise to the question, if the actual amount of renewable energy production already exceeds this share making a stop or at least a modification of its promotion necessary. Our approach proves to be robust to a change of pattern of marginal abatement costs (MAC), while resulting variances can be narrowed down and quantified. For its application to empirical data, we develop a method to evaluate the performance of the ETS and the promotion of renewable energy. On that basis we suggest modifications of the ETS to uncouple the certificate price from economical fluctuations and the development of renewable energy leading to their better combination and stronger mitigation incentives. For Germany it turns out, that the electricity generation of renewables has not exceeded its optimal share yet, while data is restricted due to low mitigation incentives set by the ETS. Therefore both the suggested improvement of the ETS and the monitoring of the development of renewable energy, referred to our model, is strongly recommended.
Keywords: 330